PENGALAMAN HUBUNGAN ROMANTIS PADA LAKI-LAKI DEWASA AWAL FATHERLESS AKIBAT PERCERAIAN ORANG TUA - Dian Hamama; Rahmadianti Aulia; Niken Hartati; Agitia Kurniati Asrila (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACK Parental divorce may result in fatherlessness, a condition characterized by the physical and emotional absence of a father figure, which can influence psychological development, including romantic relationships during emerging adulthood. This study aimed to explore the romantic relationship experiences of emerging adult men who experienced fatherlessness due to parental divorce. A qualitative approach with the Interpretative Phenomenological Analysis (IPA) method was employed. The participants consisted of two 21-year-old men selected through purposive sampling. Data were collected through semi-structured in-depth interviews, observations, and documentation, and were analyzed using the stages of IPA. The findings identified three superordinate themes: experiences of losing a father figure, the impact of fatherlessness on romantic relationships, and expectations for future relationships. Fatherlessness influenced participants’ ability to develop trust, express emotions, and establish emotional intimacy, leading them to approach romantic relationships more cautiously. However, participants also interpreted these experiences as opportunities to build healthier relationships. The study concludes that fatherlessness shapes the psychological dynamics of romantic relationships while encouraging self-reflection and a commitment to developing more adaptive relationships in emerging adulthood. ABSTRAK Perceraian orang tua dapat menyebabkan kondisi fatherless, yaitu ketidakhadiran figur ayah secara fisik maupun emosional yang berpotensi memengaruhi perkembangan psikologis, termasuk hubungan romantis pada masa dewasa awal. Penelitian ini bertujuan mengeksplorasi pengalaman hubungan romantis pada laki-laki dewasa awal yang mengalami fatherless akibat perceraian orang tua. Penelitian menggunakan pendekatan kualitatif dengan metode Interpretative Phenomenological Analysis (IPA). Partisipan terdiri atas dua laki-laki berusia 21 tahun yang dipilih melalui purposive sampling. Data dikumpulkan menggunakan wawancara mendalam semi-terstruktur, observasi, dan dokumentasi, kemudian dianalisis mengikuti tahapan IPA. Hasil penelitian mengidentifikasi tiga tema utama, yaitu pengalaman kehilangan figur ayah, dampak fatherless terhadap hubungan romantis, dan harapan terhadap relasi di masa depan. Pengalaman fatherless memengaruhi kemampuan membangun kepercayaan, mengekspresikan emosi, dan menjalin kedekatan emosional sehingga partisipan cenderung lebih berhati-hati dalam hubungan romantis. Namun, pengalaman tersebut juga dimaknai sebagai pembelajaran untuk membangun hubungan yang lebih sehat. Penelitian ini menyimpulkan bahwa pengalaman fatherless membentuk dinamika psikologis sekaligus mendorong refleksi diri dan komitmen membangun relasi yang lebih adaptif pada masa dewasa awal.